Comparative Study of Al-Azhar & Al-Mishbah's Interpretation of the Qur'an, Surah Al-Baqarah Verse 153 Regarding the Concept of Patience - Karlina, Yulis; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research entitled: "Comparative Study of Al-Azhar and Al-Mishbah Interpretations in the Qur'an Surah Al-Baqarah Verse 153 Regarding the Concept of Patience" raises a comparative study of the interpretation of Prof. Dr. Haji Abdul Malik Karim Amrullah (Buya HAMKA) in the Tafsir Al-Azhar and Prof. Dr. M. Quraish Shihab, MA in the Tafsir Al-Mishbah. The selection of this topic is due to the inaccurate understanding of the Indonesian Muslim community regarding the need for patience. Researchers often find that the meaning of patience is equated with "enduring poverty and misfortune" or being 'forced' to accept misfortune. In this context, patience falls into the "passive" or "forced" realm. Examining several verses about patience, including the command of Allah SWT to ask for help with patience and prayer (QS Al-Baqarah: 153), the researcher believes this verse and other verses of patience should be understood as "active and productive patience." This article shows that patience is a very important moral or behavior for every Muslim to maintain their honor, dignity, and status as superior Muslims. Every Muslim must be patient in receiving blessings or trials in open or narrow, easy or challenging circumstances. Prof. Hamka and Prof. M. Quraish Shihab see the essence of patience as a person's ability to control emotions to control themselves in good or harmful situations. According to Buya Hamka, patience is a noble and enlightened attitude of the soul, which is achieved through self-control, steadfastness, and persistence in all trials and gratitude to God and holding fast to piety, while according to M. Quraish Shihab, patience is restraining oneself from the tumult of the heart to achieve something good through the holiness of God.